Technology training: athletes using vibration method and technical means - Skrypko, A.; Lamcha, L. (LASE Journal of Sport Science, 2017)
The core idea behind the article is to work out a set of exercises that will use vibrostimulation combined with traditional power training, and the application of these methods in leisure activities provided to people at various ages. Study aim: 1. determination of frequency parameters under the influence of vibro-mechanical stimulation of human muscles, 2. the combination of vibrostimulation and other coaching methods and trainer`s aims to increase power, speed and suppleness of athlete joints. The test results and new technologies worked out will have an opportunity to be used in such scientific and teaching areas as: theory and methodology of sport and physical education, anthropomotorics, kinesiology, biomechanics, but first of all they will provide coaches of various sports disciplines with the sets of ready-made exercises, significantly improving innovative element in athlete coaching.